The role of systemic immune-inflammation index (SII) in the differential diagnosis of granulomatous and reactive LAP diagnosed by endobronchial ultrasonography: Evaluation of the systemic immune-inflammation index in sarcoidosis, tuberculosis and reactive lymphadenitis - Kerget, Buğra; Afşin, Dursun Erol; Aksakal, Alperen (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Background and aim: Tuberculosis and sarcoidosis are the two most important granulomatous diseases that physicians have difficulty in differential diagnosis. In our study, we aimed to observe the place of systemic immune-inflammation index (SII) level in the differentiation of patients diagnosed with endoboronchial ultrasonography (EBUS). Methods: Our study included 494 patients who applied to our hospital’s chest diseases outpatient clinic between 2015 and 2020 and underwent endobronchial ultrasonography (EBUS) for mediastinal lymphadenopathy (LAP). Patients’ follow-up for at least 2 years after diagnosis and pre-procedural hematologic parameters were retrospectively recorded. Results: In the comparison of SII between groups, it was observed that SII was statistically significantly higher in patients followed up for tuberculous lymphadenitis compared to patients with sarcoidosis and reactive LAP (p=0.01, <0.001). In sarcoidosis patients, SII levels were statistically significantly higher than in patients with reactive LAP (p=0.002). Platelet, sedimentation and SII levels were statistically significantly higher in stage 2 patients compared to stage 1 patients, while lymphocyte levels were lower (p=0.009, 0.001, 0.001, 0.001, 0.001 respectively). In the ROC curve analysis of the SII level of patients with sarcoidosis and tuberculosis LAP, the AUC was 0.668 and when the cut-off value for the SII level was 890.667, the sensitivity was 70% and the specificity was 66% in the differentiation of tuberculosis and sarcoidosis lymphadenitis. Conclusion: SII may be an easily applicable parameter in the differentiation of tuberculosis and sarcoidosis LAP with granuloma and in the differentiation of granulomatous diseases from reactive LAP.